Red-flag symptom clusters in transthyretin familial amyloid polyneuropathy - Conceição, isabel (2021)
© 2015 The Authors. Journal of the Peripheral Nervous System published by Wiley Periodicals, Inc. on behalf of Peripheral Nerve Society. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.